Prevalence of Postpartum Anoestrus in Cattle in Jabalpur - Sahu, Shilpa; Bajaj, Nitin; Gupta, Vishnu; Choudhary, Govind Prasad; Chouksey, Shivika; Shukla, SatyaNidhi (The Indian Journal of Animal Reproduction, 2022)
The present research work was planned to study the prevalence of anoestrus in cattle in and around Jabalpur. A total of 157 cows reared under field conditions (76 from organized and 81 from unorganized) in different villages situated in Jabalpur during the period of six months (June to November 2021) were surveyed and calving and breeding history of animals provided by the dairy owners was recorded. Per-rectal examination of genitalia (cervix, uterus and ovary) was also done to know the reproductive status of the animals. The observations were recorded in a prescribed proforma. The cows with a history of not showing the signs of oestrus for 90 days or more postpartum were considered for the study of the prevalence of anoestrus. The prevalence of anoestrus in postpartum cows was 19.10 per cent (30/157). The prevalence of anoestrus in organised and unorganized dairy farm was recorded to be 15.78 and 22.22 per cent, respectively. Write a conclusion based on the findings. Good managemental practice as in organized dairy farms decrease the incidence of anoestrus in cows as compared to unorganized dairy farms.
Keywords: Anoestrus cattle; Prevalence; Postpartum anestrous; Jablapur